2014
DOI: 10.3390/ani4030391
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes toward Animal Research: A Review

Abstract: Simple SummaryPublic engagement on issues related to animal research, including exploration of public attitudes, provides a means of achieving socially acceptable scientific practice and oversight through an understanding of societal values and concerns. Numerous studies have been conducted to explore public attitudes toward animal use, and more specifically the use of animals in research. This paper reviews relevant literature using three categories of influential factors: personal and cultural characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 89 publications
7
118
1
1
Order By: Relevance
“…The current debate about the use of animals in research is strongly rooted in questions related to public's perception of animals' welfare and suffering on one side, and research benefits on the other (Ormandy andSchuppli 2014; Clemence andLeaman 2016). Laboratory animals are perceived as those subjected to greater welfare violation and, as a natural consequence, people involved in researches that use animals are generally perceived to be unaware or unconcerned about this issue (Broida et al 1993; Wolfensohn andHoness 2007).…”
Section: Laboratory Animalsmentioning
confidence: 99%
“…The current debate about the use of animals in research is strongly rooted in questions related to public's perception of animals' welfare and suffering on one side, and research benefits on the other (Ormandy andSchuppli 2014; Clemence andLeaman 2016). Laboratory animals are perceived as those subjected to greater welfare violation and, as a natural consequence, people involved in researches that use animals are generally perceived to be unaware or unconcerned about this issue (Broida et al 1993; Wolfensohn andHoness 2007).…”
Section: Laboratory Animalsmentioning
confidence: 99%
“…For instance, the increase in animal use we observed that had been mainly accounted for by mice—at the same time that federal policies restricting the use of chimpanzees, dogs and cats are being enacted in response to public pressure—reflects scientists’ and laypersons’ greater moral concern for animals in laboratories who are typically viewed as companion animals or as being ‘human-like’ or having ‘higher’ mental abilities 29 30. This bias persists despite extensive evidence that—like dogs, cats and primates—animals such as mice, rats and fish experience pain, stress and distress, and suffer in laboratories and have complex social, emotional and cognitive lives 31 32…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on attitudes toward animal research have been carried out across a narrow range of high-income countries in Europe and North America, 32,33 while little research has been conducted on the attitudes of people in lowerincome and agricultural-based societies, especially in the LMICs. Furthermore, such studies tend to focus on a limited number of animal species including non-human primates; companion animals, such as dogs and cats; and laboratory animals used in biomedical research, such as mice and rats.…”
Section: Animal Researchmentioning
confidence: 99%